The decision-making in dribbling: a video analysis study of U10 soccer players’ skills and coaches’ quality evaluation - Iuliano, Enzo; Bonavolontà, Valerio; Ferrari, Dafne; Bragazzi, Nicola; Capasso, Benito; Kuvačić, Goran; De Giorgio, Andrea (Frontiers in Psychology, 2023)
Dribbling is an important soccer skill that, when effective, allows players to overcome opponents. It can provide a strong tactical advantage; for this reason, all of its components (sprint, speed, and ball control) are fundamental to the development of young players. Dribbling can also be considered a decision-making process, and due to its characteristics, it is not always easy to study ecologically. Using a video analysis study, this research aimed to determine whether dribbling skills, specifically dribbling choice (i.e., decision-making), were related to UI0 soccer players, quality. Several outcomes measures, divided into three categories, were taken during video analyses: i) measures related to the efficacy of dribbling skill; ii) measures related to the ability of players without the ball to support the player in possession; iii) measures related to ball circulation. These data were retrospectively correlated to whether the coaches had formed the teams in training through an implicit knowledge of the players" dribbling skills. The percentage of accurate dribbling (that is, the ability to perform correct passes after a successful dribble) was found to be the variable that coaches may have implicitly used in creating the three groups differentiated by technical skills. In fact, this percentage was 12.9%, 24.0%, and 48.1%, respectively, for the groups with lower, average, and higher technical skills, with significant differences among the groups (p <0.05). Overall, the results demonstrate that dribbling accuracy has an important weight in the coache's evaluation of the technical skills level of young soccer players